Flow of pH-responsive microcapsules in porous media. (17th February 2015) - Gun, Wei Jin; Routh, Alexander F.
Abstract: This article investigates the use micro-capsules, containing a gelling agent hydroxypropyl cellulose (HPC), to alter flow paths in porous media. The aim is to preferentially block-off high permeability regions, thereby diverting the flow into adjacent un-swept low permeability regions. Micro-capsules with 2–7 µm in diameter were made by polymer precipitation through solvent evaporation using poly(4-vinyl pyridine) (PVP) as the shell material. A customised flow tank was constructed to facilitate porous media flow and both single and dual permeability experiments were conducted. Even without gelling agent, the micro-capsules gradually blocked the pore throats of the glass beads network. Following acidification a drop in permeability was observed. This was because swelling of the PVP shell constricted the pore throats. The permeability drop was observed to be more significant for low permeability regions. Flowing micro-capsules through the tank with two permeability regions in parallel allowed the high permeability region to be selectively blocked. Graphical abstract: Highlights: We demonstrate the triggering of pH sensitive micro-capsules in a porous media. The flow-paths in the porous media can be affected by introducing micro-capsules. Un-triggered capsules can affect the flow and the degree of blockage depends on the pore throat and micro-capsule sizes. Increased flow through low permeability regions is demonstrated.